2010
DOI: 10.1210/jc.2009-1903
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Association Study of Bone Mineral Density in Premenopausal European-American Women and Replication in African-American Women

Abstract: Evidence of association to several novel loci was detected in a GWAS of premenopausal EA women, and SNPs in one of these loci also provided supporting evidence in a sample of AA women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
59
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(60 citation statements)
references
References 29 publications
1
59
0
Order By: Relevance
“…Although the peak level of BMD is influenced by diet and physical activity, genetic factors are also important. Studies about this issue showed that ADAMTS18 has been associated with femoral neck bone mineral density (41).…”
Section: Menopause and Adamtsmentioning
confidence: 99%
“…Although the peak level of BMD is influenced by diet and physical activity, genetic factors are also important. Studies about this issue showed that ADAMTS18 has been associated with femoral neck bone mineral density (41).…”
Section: Menopause and Adamtsmentioning
confidence: 99%
“…Estrogen receptor 1 (ESR1) at 6q25.1, (5)(6)(7)(8) low density lipoprotein receptor-related protein 4 (LRP4) at 11p11.2, (7)(8)(9) low density lipoprotein receptor-related protein 5 (LRP5) at 11q13.4, (6)(7)(8)10,11) integrin, alpha 1 (ITGA1) at 5q11.2, (8) secreted phosphoprotein 1ADAM metallopeptidase with thrombospondin type 1 motif 18 (ADAMTS18) at 16q23, (16,17) and spectrin, beta, non-erythrocytic 1 (SPTBN1) at 2p21 (5,7,9,12,18) are associated with BMD at the GWAS level. Among them, the associations between variants in ZBTB40, (10) ESR1, (10) TNFRSF11B, (10) LRP5, (10) ADAMTS18, (16) and SPTBN1 (12,18) and osteoporosis have been replicated in both European and East-Asian populations.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the importance of IBSP, encoding for bone sialoprotein 2, in various aspects of bone physiology [44], this gene has been poorly studied as a candidate in the association studies of relevant phenotypes. Thus we are aware of only two studies where IBSP gene was investigated and specifically mentioned within the framework of genetic association studies [45,46]. Both studies were designed as genome-wide association study of BMD and both provided evidence of importance of IBSP in determination of BMD.…”
Section: Discussionmentioning
confidence: 99%
“…The median levels of OPN were significantly higher in men than in women, 51.725 vs. 46.200 ng/ml (Mann-Whitney U test, p=0.022). There were significant but modest correlations between age and OPN levels in the total sample (r=0.0848, p=0.010) and in the females' sample (r=0.1776, p<0.001).…”
Section: Preliminary Statisticsmentioning
confidence: 90%